2001
DOI: 10.2141/jpsa.38.181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Stevia (Stevia rebaudiana) Extract on Gizzard Erosion and UIceration Induced by Dietary Histamine in Broiler Chicks.

Abstract: An experiment was conducted to determine if dietary Stevia (Stevia rebaudiana) extract prevents gizzard erosion and ulceration of chicks induced by dietary histamine. Day old broiler chicks were fed on a basal diet, a diet with 0.4% histamine or a diet containing 0.2% Stevia extract (on dry matter basis) +0.4% histamine for 14 days. Dietary histamine reduced growth and caused occurrence of gizzard erosion and ulceration as previously reported. Feeding of Stevia extract containing diet partly prevented retardat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In spite of many reports in mammals, to our knowledge, there is no report of plant extracts having a protective activity against the effects of dietary histamine in fish. In broiler chicks stevia extract has previously been shown to reduce the action of histamine (Takahashi et al . 2001b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In spite of many reports in mammals, to our knowledge, there is no report of plant extracts having a protective activity against the effects of dietary histamine in fish. In broiler chicks stevia extract has previously been shown to reduce the action of histamine (Takahashi et al . 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…2001b). Takahashi and colleagues (2001b) suggested that the gastric protective activity of stevia extract in broiler chicks is because of (1) anti‐oxidant activity, (2) inhibition of histamine incorporation from intestine, (3) activation of histamine catabolism, (4) blocking of H2‐histamine receptor, (5) inhibition of H + /K + ATPase or (6) inhibition of peptic activity. In the present study the activation of pepsin in the gastric mucosa by dietary histamine was seen and the pepsin activity in the gastric irrigation solution was slightly increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to vasodilatation, stevia reduced gastric mucosal damage induced by histamine in rainbow trout [21]. Stevia prevented increased contractility of the gastrointestinal smooth muscle evidenced by its antispasmodic effect in guinea pig ileum and reduced gizzard erosion in broiler chickens fed dietary histamine [21][22][23]. Moreover, stevia was suggested to be gastroprotective by regulating gastric acid secretion and preventing gastric ulcer formation in a similar manner to that of calcium channels blockers (CCB).…”
Section: Electrophysiological Vasoactive and Gastromodulatory Effecmentioning
confidence: 99%